Designing Technology for less literate people with diabetes in Punjab, Pakistan - KEHKASHAN ZEB (2024)
Digital health uses information communication technology to provide healthcare services ef-fectively. This research uses Human-Computer Interaction methodologies such as participatory design and iterative prototype evaluation to effectively design technology for people in the rural areas of Punjab, Pakistan.Many participants in this PhD research have a low literacy level, making it challenging for them to obtain the knowledge necessary to manage their common chronic health conditions, such as diabetes. The remoteness of these participants, the lack of transport, and the internet inaccessibility only exacerbate this healthcare self-management. The research focused on designing an Interactive Voice Response system using participatory design methodologies.Interactive Voice Response (IVR) is an accessible method of transmitting knowledge because it allows voice-based interaction. To assist illiterate populations in managing chronic health conditions, hierarchical IVR systems are currently being developed and pose the challenge of navigating a large amount of information with hierarchy. Therefore, using a phone number-specific profile, this project iteratively develops a dynamic IVR that adapts information presen-ted to people with diabetes to compensate for some of their challenges in healthcare support. Multiple design studies and deployments are conducted to validate the IVR system.The IVR system was designed iteratively using Participatory Design (PD) to explore users’ pref-erences. Although PD originated in Scandinavia, it poses several challenges since it assumes literacy and a cultural mindset associated with the Global North. Hence, it is necessary to adopt democratic, patient-centred, iterative participatory approaches to develop a comprehensive understanding of PD in a diverse and challenging environment, including both urban and rural contexts. Several PD techniques were used, including Wizard of Context, Narrative Scoping with Personas, an interactive framework that used videos, pictures and audio, and iterative PD.After deploying the IVR system using servers built on the Asterisk platform, the system’s usefulness for keeping people with diabetes informed about their condition and better managing their condition was demonstrated by gathering qualitative and quantitative data.